Diagnosis Dan Penatalaksanaan Diare Persisten Dengan Gizi Buruk Dan Anemia - Rosi Indah Pratama; Dara Marissa Widya Purnama (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2018)
Introduction: Diarrhea is the changing of feces consistency in a sudden time due toamount of water in feces increase more than normal and the frequency of defecation is more than 3 times in 24 hours. Diarrhea is second cause of mortality of children less than five years old in the world. Persistent or chronic diarrhea is one health problems that influence child mortality level in the world.Ilustration case: a 2 years old girl with major complaint of watery faces 7 days before go to hospital. 1,5 months ago, had the same history and had been treated in intensive care unit.Physical Examination: had sunken eyes, anemi conjunctiva, dry and pale lip, and turgor turn back slower.Laboratrium Examination: albumin 2,5, Hb 8g/dl, hematocrit 29%, thrombosit 945.000/ul, Calcium 7,5. Conclusion: hypoalbuminemia, microcytic hypochromic anemiar dd deficiency of Fe, thrombocytosis dan hypocalcemia. The results of feces cultur found gram negative bacteria that sensitive with amikasin, meropenem and netilimicyn.Management: Administration of Oralit, zinc tablets for 10 consecutive days, continuing to eat, antibiotics selectively and advice on mother / family.Discussion: Diarrhea occurs 2 months before admission to hospital despite hospitalization. The episode supports the diagnosis of persistent diarrhea. Malnutrition is a risk factor for persistent diarrhea. Lack of absorption of nutrients including iron and feces carry a lot of fluids and electrolytes resulting in anemia and electrolyte imbalances of patients. Lack of nutrient intake causes the breakdown of protein and fat for energy needs so that hypoalbumin can occur. Provision of antibiotics in accordance with the results of feses culture.